Manajamen Pembinaan Santri dalam Mengembangkan Prestasi Non Akademik di Pondok Pesantren Al-Murtadlo Ponjong Gunungkidul - Janingsih Janingsih; Fahmi Zen; Hendy Pratama; Anaas Tri Ridlo Dina Yuliana; Fadhlurrahman Fadhlurrahman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Al-Murtadlo Islamic Boarding School Ponjong Gunungkidul is an Islamic-based educational institution that not only emphasizes religious education, but also develops the non-academic achievements of students. This research aims to determine the management of student development in developing non-academic potential, such as martial arts, MTQ, sports and arts. This research uses descriptive qualitative research methods with data collection techniques using observation, interviews and literature study. The collected data was analyzed using the Miles and Huberman model, which includes data reduction, data presentation, and drawing conclusions. (Zulfirman, 2022) It was found that coaching was carried out through three main stages: talent and interest selection, ability grouping, and intensive training. Supporting factors include professional trainers, adequate infrastructure and effective time management. The non-academic achievements achieved by students reflect character formation, such as responsibility, discipline and cooperation. In addition, the integration of religious education and non-academic development makes a significant contribution to the formation of a generation of students who are spiritually and socially competent. This Islamic boarding school is an ideal example of an Islamic educational institution that is responsive to the needs of modern society.